Design and fabrication of terahertz antenna arrays with integrated graphene modulators on 8-inch wafers - Silva, Rui (2024)
The Terahertz band is considered the next frontier for wireless communications, leading to unprecedent available bandwidth, enabling unforeseen end-user devices technologies, supported by the announced 6G technologies that will make use of this band, or enabling new technological solutions at the sensing or medical application level.